2012
DOI: 10.1364/oe.20.015797
|View full text |Cite
|
Sign up to set email alerts
|

Multipolar second harmonic generation from planar arrays of Au nanoparticles

Abstract: We demonstrate optical Second Harmonic Generation (SHG) in planar arrays of cylindrical Au nanoparticles arranged in periodic and deterministic aperiodic geometries. In order to understand the respective roles of near-field plasmonic coupling and long-range photonic interactions on the SHG signal, we systematically vary the interparticle separation from 60 nm to distances comparable to the incident pump wavelength. Using polarization-resolved measurements under femtosecond pumping, we demonstrate multipolar SH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
50
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 37 publications
0
50
0
Order By: Relevance
“…The electron concentrations are spread out well away from the center, and also create incoherent multipolar resonances throughout the spiral. The second-harmonic radiation produced by these physically separate resonances destructively interferes with itself as expected from SHG produced by a spatially symmetric set of electronic dipole resonators [14]. These symmetry effects are evident from brighter edges of the spiral in the simulations.…”
mentioning
confidence: 77%
See 2 more Smart Citations
“…The electron concentrations are spread out well away from the center, and also create incoherent multipolar resonances throughout the spiral. The second-harmonic radiation produced by these physically separate resonances destructively interferes with itself as expected from SHG produced by a spatially symmetric set of electronic dipole resonators [14]. These symmetry effects are evident from brighter edges of the spiral in the simulations.…”
mentioning
confidence: 77%
“…High efficiency is therefore also crucial in order to generate reasonable numbers of photons in nonlinear processes without melting or damaging the nanostructures. A periodic arrangement of centrosymmetric nanoparticles offers one route to enhanced nonlinear signals [14]. Creating non-centrosymmetric systems of parBrought to you by | MIT Libraries Authenticated Download Date | 5/11/18 12:30 PM ticles with a center of inversion symmetry yields even greater harmonic conversion efficiencies [15].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The history of mathematical phyllotaxis started in the first half of the nineteenth century when the brothers Auguste and Louis Bravais presented the first quantitative treatment of the phenomenon and recognized the relevance of the theory of continued fractions in this area (i.e., in the so-called cylindrical representation of phyllotaxis) [70]. Aperiodic Vogel spiral arrays of nanoparticles are rapidly emerging as a powerful nanophotonics platform with distinctive optical properties of interest to a number of engineering applications [42,58,[71][72][73][74][75][76][77][78]. This fascinating category of deterministic aperiodic media features circularly symmetric scattering rings in Fourier space entirely controlled by simple generation rules that induce a very rich structural complexity.…”
Section: Structural Properties Of Aperiodic Arraysmentioning
confidence: 99%
“…Moreover, it has been recently demonstrated that Vogel spiral arrays of metallic nanoparticles feature distinctive structural resonances and produce polarization insensitive, planar light diffraction across a broad spectral range, referred to as circular light scattering [72]. The planar diffraction property of Vogel spirals is ideally suited to enhance light-matter interactions on planar substrates and recently led to the demonstration of thin-film solar cell absorption enhancement, light emission, and second harmonic generation enhancement using metal-dielectric arrays [42,77,78]. Another fascinating feature of Vogel spiral diffracting elements is their ability to support distinctive scattering resonances encoding well-defined numerical sequences in the orbital angular momentum (OAM) of light [72][73][74][75], potentially leading to novel applications to singular optics and optical cryptography [79].…”
Section: Structural Properties Of Aperiodic Arraysmentioning
confidence: 99%